2022
DOI: 10.1186/s12884-022-04655-6
|View full text |Cite
|
Sign up to set email alerts
|

Atypical fetal junctional ectopic tachycardia: a case report and literature review

Abstract: Background Junctional ectopic tachycardia (JET) is caused by ectopic rhythms, originating in the atrioventricular node, typically with heart rate between 200 and 250 bpm. Herein, we present a case of fetal JET with normal fetal heart rate and a review of nine cases. Case presentation A 32-year-old, gravida 2, para 1, woman in whom fetal JET could not be diagnosed prenatally because the fetal heart rate was within the normal range. The fetus was dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Most cases of fetal tachycardia have a heart rate of less than 200 bpm, which usually does not require treatment but requires close follow-up[ 1 , 2 ]. Approximately 10%–20% of cases of fetal tachycardia require referral to a fetal cardiologist for further evaluation, and persistent fetal tachycardia with congestive cardiac dysfunction or fetal edema requires intrauterine or postpartum treatment[ 3 , 4 ]. One report of FHR > 224 bpm indicated that the persistence of fetal tachycardia was not necessarily caused by fetal hypoxia, and the heart rate was controlled by metoprolol treatment after transfer to a higher-grade hospital[ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of fetal tachycardia have a heart rate of less than 200 bpm, which usually does not require treatment but requires close follow-up[ 1 , 2 ]. Approximately 10%–20% of cases of fetal tachycardia require referral to a fetal cardiologist for further evaluation, and persistent fetal tachycardia with congestive cardiac dysfunction or fetal edema requires intrauterine or postpartum treatment[ 3 , 4 ]. One report of FHR > 224 bpm indicated that the persistence of fetal tachycardia was not necessarily caused by fetal hypoxia, and the heart rate was controlled by metoprolol treatment after transfer to a higher-grade hospital[ 5 ].…”
Section: Discussionmentioning
confidence: 99%